Macroeconomic Fluctuations in the Caribbean : The Role of Climatic and External Shocks - Sosa, Sebastian (IMF Working Papers; Working Paper ;, 2009)
This paper develops country-specific VAR models with block exogeneity restrictions to analyze how exogenous factors affect business cycles in the Eastern Caribbean. It finds that external shocks play a key role, explaining more than half of macroeconomic fluctuations in the region. Domestic business cycles are especially vulnerable to changes in climatic conditions, with a natural disaster leading to an immediate and significant fall in output-but the effects do not appear to be persistent. Oil price and external demand shocks also contribute significantly to domestic macroeconomic fluctuations. An increase in oil prices (external demand) is contractionary (expansionary), and the effects dissipate up to three years after the shock.